PENGARUH PERSEPSI HARGA DAN TAGLINE “GRATIS ONGKIR” TERHADAP KEPUTUSAN PEMBELIAN IMPULSIF SECARA ONLINE PADA MASYARAKAT PENGGUNA APLIKASI SHOPEE DI DESA BARIBANIAEK, KECAMATAN MUARA - Ridhon Simangunsong; Risna Uli Sihombing; Srianjelina Siregar (Jurnal Ilmu Sosial Dan Politik, 2022)
This study aims to determine how big the influence of Price Perception and Shopee's "Free Shipping" Tagline on Impulsive Online Purchase Decisions in Shopee Application Users in Baribaniaek Village, Muara District, either partially or simultaneously. This type of research is quantitative. The population in this study is the Shopee Application User Community in Baribaniaek Village, Muara District. The sampling technique in this research is non-probability sampling, namely purposive sampling with a sample size of 96 respondents. The types of data used are primary data and secondary data. Data collection techniques with questionnaires via google form. The data analysis method used is an instrument test consisting of validity and reliability tests, classical assumption test consisting of normality test, multicollinearity test and heteroscedasticity test, multiple linear regression test and hypothesis testing consisting of t-test, f-test, and coefficient of determination (R2). The results showed that price perception had a positive and significant effect on purchasing decisions, this was indicated by the value of tcount (5,994) > ttable (1.984) and the significant value of the price perception variable was 0.000 < 0.05. Shopee's "Free Shipping" tagline has a positive and significant effect on Purchase Decisions, this is indicated by the value of tcount (7,313) > ttable (1,984) and the significant value of Shopee's "Free Shipping" Tagline variable is 0.000 < 0.05. Simultaneously, it is known that Price Perception and Tagline "Free Shipping" have a positive and significant effect on Impulsive Purchase Decisions, this is indicated by the value of fcount (7,072) > ftable (3.09) and a significant value of 0.000 <0.05. The coefficient of determination obtained is 0.629, meaning that the Purchase Decision variable can be explained by the Price Perception variable and the "Free Shipping" tagline of 38,2% While the remaining 61,8% is explained by other variables not explained in this study.